If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 96 = 12f Solving 96 = 12f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-12f' to each side of the equation. 96 + -12f = 12f + -12f Combine like terms: 12f + -12f = 0 96 + -12f = 0 Add '-96' to each side of the equation. 96 + -96 + -12f = 0 + -96 Combine like terms: 96 + -96 = 0 0 + -12f = 0 + -96 -12f = 0 + -96 Combine like terms: 0 + -96 = -96 -12f = -96 Divide each side by '-12'. f = 8 Simplifying f = 8

| 8(m-5)=2(2m-8) | | -9x-15y=6 | | 5x+8=-12 | | 14u=70 | | 6x+2x+6=5(x-3) | | 3c+4=-4c-14 | | y=-x+7 | | 6x+2=3x+8 | | 15s=120 | | x^2+18xy+81y^2=0 | | 35htq=5 | | 5x+4x+1=19 | | x^2+17x+72=0 | | 72=0.6r | | 4(4d)-18-3d=32 | | 4(2d)-18-3d=32 | | 08b=1.12 | | 2.3g=7.13 | | 3x+7-2=8 | | 40=1.6m | | m-3=8 | | 5+3(4n+2)-n= | | 5(x-7)=10 | | 10=z+3 | | 4x^3=9x^2 | | b^4-1296= | | -2+13=6b-3-5b | | y-2=0 | | -17x=255 | | y+2.3=5.6 | | 12s-14s=8 | | 7-7=10t-3t | | (2t+5)=3 | | 4y-7y=12 | | 3s^2=7s | | (m)=8 | | -720=-20(-4b) | | 105-90=32y-37y | | 6t-t-3=4t-4 | | b^2=3b | | -15=15(h-2) | | 7t-t-6=5t-5 | | 3(2a-5b+6)= | | 19=6x-11 | | -3(6n-6)+3n= | | 6(c-7)=7(c-8) | | -71+15y+3=5(5y-4)-8 | | 2y(y+4)=10 | | -4(3p+3)-18=3(4p+6) | | 5x-9=11x-15 | | 18x^3=4 | | 9x+4(3-x)=7(3) | | 3x-36=4+x | | (6x+7)(4x-7)=0 | | X=199-99 | | 18-3x=2+x | | X-(5-3x)= | | 200+13-27+3= | | 210+13-27+3= | | 190+13-27+3= | | 30+61+5= | | 4(c+5)-2c=12 | | -5y=60 | | -32=8m | | 0.2x+160=x+80 |